1996
DOI: 10.1210/jc.81.3.1147
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of transient congenital hypothyroidism due to maternal thyrotropin receptor-blocking antibodies in over one million babies

Abstract: "Incidence of transient congenital hypothyroidism due to maternal thyrotropin receptorblocking antibodies in over one million babies" (1996). Open Access Articles. 987.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1
7

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(76 citation statements)
references
References 0 publications
2
66
1
7
Order By: Relevance
“…Mães com doença tiroidiana autoimune poderiam ter mais de um filho afetado devido à persistência de anticorpos anti-receptores do TSH por vários anos. As manifestações podem ser diferentes em cada um dos filhos: bócio, hipertiroidismo ou hipotiroidismo (8,22). Nesses casos, a função tiroidiana do recém nascido pode retornar ao normal dentro de 3 a 6 meses (2).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Mães com doença tiroidiana autoimune poderiam ter mais de um filho afetado devido à persistência de anticorpos anti-receptores do TSH por vários anos. As manifestações podem ser diferentes em cada um dos filhos: bócio, hipertiroidismo ou hipotiroidismo (8,22). Nesses casos, a função tiroidiana do recém nascido pode retornar ao normal dentro de 3 a 6 meses (2).…”
Section: Discussionunclassified
“…Brown e cols. (22) avaliaram mais de 1.600.000 bebês submetidos à triagem neonatal em um período de 6 anos nos Estados Unidos. De 788 crianças com suspeita de hipotiroidismo congênito, nove apresentavam TRAB positivo, resultando numa incidência de HCT por anticorpos maternos de aproximadamente 2% dos casos.…”
Section: Discussionunclassified
“…Pop et al revealed decrease in the intelligent quotient of children aged 5 years whose mothers were TPO antibody positive at 32 weeks of gestation even though they were actually euthyroid(12). Brown and co-workers in 1996 did a study on over one million babies and found that only 1 in 180,000 neonates born to mothers with Hashimotos thyroiditis had thyroid dysfunction (13).…”
Section: Clinical Features Of Hypothyroidismmentioning
confidence: 99%
“…TRAb testing may be used to ascertain the risk for neonatal thyrotoxicosis, which occurs in approximately 2% of pregnant women with GD. TRAb tests should be performed in the third trimester to predict this particular thyroid dysfunction when there is previous history of neonatal hyperthyroidism or when the mother has GD or has had GD in the past (96,101) (D,B).…”
Section: (Bb)mentioning
confidence: 99%